Building Business Competition Law in Indonesia Based on Islamic Economic Principles - Khairul Wahid; Yuliani (MAQOLAT: Journal of Islamic Studies, 2023)
.  Law Number 5 of 1999 entitled Prohibition of Monopolistic Practices and Unfair Business Competition regulates business competition law in Indonesia. One of the main reasons for the emergence of this Act was due to pressure from the IMF (International Monetary Fund) as part of the Letter of Intent (LOI) at that time. Consequently, no attempt was made to reflect Islamic values ​​in the drafting of the law. This can be seen from the exceptions in Article 50, especially the exceptions for small entrepreneurs. This research is a normative juridical research with qualitative analysis method, and the data that the writer uses is secondary data which consists of primary and secondary legal materials. The ideal law is a law that is made in accordance with the noble values ​​of society, and must also take into account the religious values ​​that are adhered to by the community. Renewal is needed in Indonesia's business competition law by integrating Islamic values ​​to create a business competition law that reflects God's values ​​and at the same time reflects the values ​​of the Pancasila Economic System